AB0556 Incidence and risk factors of infections in systemic necrotizing vasculitis. (15th June 2017) - Pena, CE; Pera, M; Costi, C; Lucila, G; Castellani, P; Nuccetelli, Y; Garcia, M
Abstract : Background: Infections in patients with systemic vasculitis represent one of the main causes of mortality. Risk factors of infection such as corticosteroid use, intensity of immunosuppressive therapy, age, presence of leucopenia, lymphopenia, hypogammaglobulinemia, associated organic involvement, and dialysis dependence have been identified Objectives: a)To determine the incidence of infection in patients diagnosed with:Polyangeitis with Granulomatosis (GPA), Eosinophilic Polyangiitis with Granulomatosis (EGPA), Microscopic Polyangeitis (PAM) and Panarteritis Nodosa (PAN), b) clinical characteristics and associated risks factors. Methods: Analytical, observational, retrospective study. Data source:clinical records of patients diagnosed with ANCA associated vasculitis and Panarteritis Nodosa, evaluated in a center of rheumatology (2000–2016). Variables:Demographic data, clinical manifestations, laboratory data, infectious events serious (requiring hospitalization or prolonged antibiotic/antiviral treatment, recurrences of herpes zoster virus or opportunistic infections), sites of infection, isolated microorganisms, mortality related to the infectious event Results: 80 patients, 61.25% women. Mean age at diagnosis: 49.2 years (range 18–77). Types of vasculitis: 41.2% GPA, 18.7% EPGA, 26.25% PAM, 3.73% PAN not associated with HBV and 10% ANCA-associated vasculitis that did not met classification criteria. Systemic involvement (68%), pulmonary (59%), renal (58%) and otorhinolaryngology (43.6%) were the most frequent. 36 infectious events were recorded in 28 patients. Follow-up time: Median 22 m (IQR6–64). Incidence of infection:38.4%, with a median of 3 m (IQR 1–18 m) from diagnosis of vasculitis. Low respiratory infections (40.7%), sepsis (39.3%), and urinary tract infections (15%) were the most common. 25% of these patients presented a second infectious event, being low respiratory tract the most frequent site (47%). Two patients had a 3rd event (soft tissue infection, septic shock). Bacterial etiology was the most prevalent (45%).Mortality at the 1st event was 14.3% (n: 4). 71.4% of patients were in the induction phase of treatment. Immunosuppressants used prior to infectious event: cyclophosphamide (48.1%), azathioprine (11.1%), methotrexate (7.4%), mofetil mycophenolate (3.7%), none (22.2%). Corticosteroids ≥30 mg/d were observed in 35.7% patients, ranging from 7.5–30 mg/d (10.7%), and ≤7.5 mg /d in 35.7%. Presence of leukopenia (26%), lymphopenia (44%), hypoalbuminemia (24%), renal insufficiency (63%) and dialysis dependency (37%) were identified in patients with infectious events. Renal involvement (p0.01) and dialysis dependence (p0.001) were significantly associated with infection. Conclusions: The incidencia of infection was 38.4%.Lower airway infections, septicemia and urinary tract infections are the most commonly implicated sites. Most infections occurred in the induction phases of the disease. Dialysis dependence and presence of renal involvement were significantly associated with the presence of infection. References: Debouverie O.Infections Events During the Course of Systemic Necrotizing Vasculitis A retrospective study of 82 cases. La Revue de Medicine Interne 2010; 35: 636–642. Kronbickler A. Frecuency, risk factors and prophylaxis of infection in ANCA-associated vasculitis. Eur J Clin Invest 2015; 45 (3): 346- 368. Disclosure of Interest: None declared